The first reported case of human tick paralysis in Brazil: a new induction pattern by immature stages - Almeida,RAMB (2012)
Tick paralysis (TP) is a rare disease with rapid progression and potential fatal evolution. Immediately after the diagnosis, removal of all ticks from the body of the patient is mandatory. The present study reports for the first time a human case of the disease in Brazil. The patient had loss of muscle strength, decreased reflexes and marked palpebral ptosis. Six hours after removal of the last tick, the ptosis improved and on the following day, the patient had near total regression of the symptoms. This report emphasizes the possible presence of similar cases that should be promptly diagnosed and quickly treated. A new induction pattern for TP in humans associated with immature stages of ticks is also presented.